Yuni's Resistance in Yuni's Novel By Ade Ubaidil and Kamila Andini - Hidayah Budi Qur’ani; Tuti Kusniarti; Desy Rufaidah (Pelopor Publikasi Akademika, 2024)
Resistance is a defensive attitude, trying to fight, oppose, or other opposition efforts in general. Resistance or resistance to something suppressed in everyday life is natural, from the inferior to the superior. A defensive attitude is also shown in the novel Yuni by Ade Ubaidil and Kamila Andini through the main female character, Yuni. Yuni's character struggles because of the stigma that exists in the community where she lives so that women cannot develop positively. Yuni is a teenager who dares to fight directly when she experiences injustice. Yuni's resistance or resistance allowed her to do what she thought was right. Yuni's resistance is in line with James C. Scott's theory. The data source in this study is the novel Yuni by Ade Ubaidil and Kamila Andini. The research data is excerpts of sentences and phrases describing Yuni's character's resistance. The results of this study are depictions of resistance forms, including (1) refusing to marry young, (2) liking purple, (3) giving up virginity, and (4) the role of parents in decision-making for Yuni's figure.